Risk Assessment and Community Capacity Level to Community Preparation for Sustainable Dengue Problem Solution in Boutue Sub-district, Songkhla Province - จันมณี, จิตรทิพย์; สุวรรณบํารุง, ผู้ช่วยศาสตราจารย์ดร.จรวย (Journal for Developing the Social and Community, 2015)
The objectives of current study were to evaluate the risk assessment and community capacity assessment in total of district and each village. Methods: Mixed method of data collecting and community participatory approach were using on five communities in Boutue Sub-district, Songkhla Province. First phase: community preparation, leader and non-leader. Second phase: risk assessment based on secondary data collection, interview of the health provider, one group discussion per village, and leader capacity assessment of the 123 leaders (123 households) with 14 domains of leader assessment tool (115 items), and non-leader capacity assessment of the 572 non-leaders (572 households) with11 domains of non-leaders (83 items) Data collection and analysis of community capacity were descriptive statistic and comparative mean statistic among domains and villages. Thematic analysis was used for qualitative data of group discussion and open end question. Third phase: Data feedback to community for preparation plan in each village. Results: There were the high level of leader capacity (ܺത ; SD : 347 ; 50.8), the moderate level of non-leader (ܺത ; SD : 227 ; 53.9)and differential statistics significant between of total leader capacity and non-leader capacity (p<.05). The domain “Religion leader capacity” and “Dengue working group” were low capacity level. Larval indices level of the district were high (BI=134.5; HI=57; CI=13.4). The district was hinge risk dengue problem and devising in three groups: high, moderate, and low level. Moo 5 (BanPou village)was higher risk score than other villages and found high larval indices (BI=128.9; HI=55.2; CI=14.5), leader capacity was low level (ܺത ; SD : 324 ; 58.4), whereas non-leader capacity was moderate level (ܺത ; SD : 214.8 ; 57.2). Whereas, Moo 4 (Watpradu village) was the low risk of dengue. The community capacity showed the high level of leader capacity (ܺത ; SD : 375.1 ; 43.3), and moderate level of non-leader capacity (ܺത ; SD : 236.0 ; 55.1). However, the larval indices were high (BI=156.9; HI=60.2; CI=13.1). Three villages (moo 1; 2; and 3) were moderate level of leader capacity, and high level of non-leader. Moreover, thematic analysis found several themes of problem and suggestion. Conclusion, dengue risk area assessment and community capacity level assessment.